Ecological evolution of salmonids - V. N. Dolganov (Известия ТИНРО, 2024)
For the first time, ecological evolution of salmonid fishes is analyzed using the method of historical biogeography, considering formation of ecology and reproductive biology for these species under planetary climatic and geological changes. Climate cooling in the Cenozoic and associated reconstruction of the food base for salmonids had a major impact on evolution of their ecology. This process began at the Asian coast of the North Pacific much earlier than at the American coast and was much more intense there. The salmonids developed marine and oceanic feeding that led to their stocks increasing and a subsequent imbalance with freshwater prey. Adapting to this imbalance, the species of gen. Oncorhynchus came to irreversible reduction of organs and functions in the fresh water and absolute mortality of producers. Egg development lengthened in cold environments, and anadromous and semi-anadromous salmonid species were forced to spawn earlier, so that the larvae would hatch during the spring bloom of their prey. Gradually, the timing of their spawning shifted from early spring to winter and then to fall; accordingly, the spawning run to the rivers began earlier, in particular in the northern areas. The spawning season of atlantic salmon Salmo salar and brown trout Salmo trutta shifted to a fall and spring-summer spawning run in the north of their range and to a winter-spring and fall spawning run in the south of their range, but there is currently no reason to consider these runs as seasonal races, given that both cases evolved from a single run in the process of evolutionary changes when the spawning season was interrupted by either winter cooling or summer warming in the lower river reaches and at the coast. The northern and southern populations of salmonid fishes in the Pacific separated, too, because of these ecological changes in the late Pliocene, in conditions of cold climate. Being in isolation, they diverged enough to be considered as separate taxa rather than seasonal races.